Expression of lectin and defensin genes in Mironovskaya 808 and Roazon wheat cultivars infected with Pseudocercosporella herpotrichoides - Belava, V.N.; Zeleniy, S.B.; Panyuta, O.O.; Taran, N.Yu.; Pogribniy, P.V. (Вiopolymers and Cell, 2010)
Aim. The dynamics of expression of protective proteins (lectin and defensin) genes of different genotypes of the winter wheat, affected by P. herpotrichoides, was investigated. Methods. RT-PCR was used for gene expression analysis. Results. We established that the lectin mRNA content in control and infecting plants of the resistant cultivar is considerably higher than in the susceptible one; the character of defensin mRNA accumulation in the investigated cultivars, control and infecting plants, does not change. Conclusion. The spare pool of lectin mRNA in the resistant cultivar is more substantial, than in the susceptible one, that is, possibly, one of the factors of the plant resistance. Inability to support constantly a high level of the protective genes expression seems to influence negatively on the cultivar resistance . Цель. Исследовать динамику экспрессии генов защитных белков (лектина и дефенсина) разных генотипов озимой пшеницы, пораженных P. herpotrichoides. Методы. Экспрессию генов определяли при помощи реакции RT-PCR. Результаты. Содержание мРНК лектина в контроле и при инфицировании P. herpotrichoides у относительно резистентного сорта (Roazon) значительно выше, чем у восприимчивого (Мироновская 808). Характер содержания мРНК дефенсина у исследуемых сортов в контроле и при инфицировании не меняется, но границы колебаний абсолютных значений у восприимчивого сорта шире. Выводы. Запасной пул мРНК лектина у резистентного сорта гораздо массивней, чем у восприимчивого, что, вероятно, является одной из составляющих устойчивости сорта. Неспособность поддерживать постоянно высокий уровень экспрессии генов защитных соединений негативно влияет на устойчивость сорта. Мета. Дослідити динаміку експресії генів захисних білків (лектину та дефенсину) різних генотипів озимої пшениці, уражених P. herpotrichoides. Методи. Експресію генів визначали за допомогою RT-PCR. Результати. Вміст мРНК лектину у контролі та за інфікування P. herpotrichoides у відносно резистентного (Roazon) сорту вищий, ніж у сприйнятливого (Миронівська 808). Характер накопичення мРНК дефенсину у досліджуваних сортів у контролі та за інфікування не змінюється, але межі коливання абсолютних значень у сприйнятливого сорту ширші. Висновки. Запасний пул мРНК лектину у резистентного сорту набагато масивніший порівняно зі сприйнятливим, що, можливо, є однією із складових стійкості сорту. Нездатність підтримувати постійно високий рівень експресії генів захисних сполук негативно впливає на стійкість сорту.